Heterogeneity in returns to agricultural technologies with incomplete diffusion: Evidence from Ghana - Sadick Mohammed; Awudu Abdulai (Review of Development Economics, 2021)
In this study, we employ a dynamic treatment effect approach to analyze heterogeneity in returns to farmers at different stages of adoption of a newly introduced inoculant technology, using a recent survey data of 600 soybean farmers from northern Ghana. Although farmers differ in their returns to adoption of new technologies, many empirical studies often fail to account for this heterogeneity. The empirical results reveal that farmers who are at advanced stages of adoption appear to, on average, more than double their yields and farm net returns, suggesting that the inoculant technology may be a game changer in the fight against extreme poverty in the region, where poverty is endemic and crop yields are persistently below the average potential yield target. Our findings further reveal that extension services as well as efficient input and output markets are key to the adoption process, by influencing knowledge acquisition, adoption, and continued adoption. Our findings also show significant impact heterogeneity at each adoption stage, with the long-term benefits of the inoculant technology outweighing its short-term benefits.
Keywords: 330; dynamic treatment effect; impact heterogeneity; inoculant~technology adoption; multistage decision-making